“Modelo de Gestión para la Carrera de Administración de Empresas De La Universidad Técnica de Cotopaxi” - Reyes Changoluisa, Jessica Valeria (2020)
This project aims to implement a Management model for the Business Administration career, to improve processes and support the articulation of the substantive functions of teaching. In this project, the processes and activities that will facilitate planning and the organization to achieve the objectives proposed as a career, are specified. To reach this goal, a current diagnosis of the career was developed. This allowed us to identify in the first instance its strengths, weaknesses, opportunities, and threats it faces. To develop this project, it was necessary to review the theoretical foundation to sustain the way forward. To develop a collection of information from primary and secondary sources. In the primary sources, interview techniques were used to collect the information. Working directly with those involved in each process, this served to identify the processes and activities that are currently being developed and also to propose their improvement to easily achieve their objectives. With all this information the management model proposal was designed for the career, which consists of many administrative elements that allow advancing easily the articulation of the substantive functions of the career, benefiting the directive part, teachers, and students.